Impact of Ergot Alkaloids on Female Reproduction in Domestic Livestock Species - Rebecca K. Poole; Daniel H. Poole (Toxins, 2019)
Fescue toxicosis is a multifaceted syndrome that elicits many negative effects on livestock consuming ergot alkaloids produced by endophyte-infected tall fescue. The economic losses associated with fescue toxicosis are primarily due to reproductive failure including altered cyclicity, suppressed hormone secretion, reduced pregnancy rates, agalactia, and reduced offspring birth weights. For decades, a multitude of research has investigated the physiological and cellular mechanisms of these reproductive failures associated with fescue toxicosis. This review will summarize the various effects of ergot alkaloids on female reproduction in grazing livestock species.